OPTIMUM PRODUCTION AND CHARACTERIZATION OF BIODIESEL FROM MICROCYSTIS AERUGINOSA ALGAE - BABATOPE OLUFEMI; SALEEM SULAIMON; ADEWALE ARIKAWE (Journal of Engineering Studies and Research)
This work examined the optimum production and characterization of biodiesel from Microcystis aeruginosa (M. aeruginosa). Optimization with Minitab software was used to design the experiment using Central Composite Design (CCD). The found optimum values of the solvent to biomass ratio, extraction temperature and time were 6.5:1, 60 oC and 144 minutes respectively. Validation of the optimum conditions for the lipids extracted was done to produce biodiesel. The average yield of the algal oil was found to be 26.7 %. The extracted algal oil was subjected to chemical transesterification using ethanolic-NaOH as catalyst and the biodiesel yield was 89.76 %. Fourier Transform Infrared Spectroscopy (FTIR) carried out on the produced biodiesel showed strong intensity of –C=O ester bond. Other characterizations done confirmed commendable suitability with conventional diesel properties.